African Demography. (September 2013) - Guengant, Jean-Pierre; May, John F.
Like many other countries worldwide, Africa faces a rapidly increasing elderly population; however, most African countries also still have very high levels of fertility, high rates of population growth, and very young populations. This means African countries will have to address the doubling or even the tripling, by 2050, of their working-age population and better prepare for the future of their upcoming young generations, while aiming for a "modern" demographic regime of low mortality and low fertility. Such a regime would put African countries in a position to capture a demographic dividend, realize inclusive growth, reduce poverty levels, and achieve economic convergence. Socioeconomic advances help foster demographic transformations, and improvements in demographic indicators also help trigger socioeconomic advances, but this process is not automatic. Authorities will need to intervene swiftly on mortality, and particularly on fertility, through adequate population and health policies and programs.